Genome-Wide Scanning for Signatures of Selection Revealed the Putative Genomic Regions and Candidate Genes Controlling Milk Composition and Coat Color Traits in Sahiwal Cattle - Illa, Satish Kumar; Mukherjee, Sabyasachi; Nath, Sapna; Mukherjee, Anupama (Frontiers in Genetics, 2021)
In the evolutionary time scale, the selection shapes the genetic variation and alters the architecture of genome in the organisms. Selection leaves detectable signatures at the genomic coordinates that provides clues about the protein encoding regions. Sahiwal is a valuable indicine cattle adapted to tropical environments with desirable milk attributes. Insights into the genomic regions under putative selection may reveal the molecular mechanisms affecting the quantitative and other important traits. To understand this, the present investigation was undertaken to explore signatures of selection in the genome of Sahiwal cattle using high-density genotyping using INDUS chip . De-correlated composite of multiple signals (DCMS),which combines five different univariate statistics was computed in the dataset to detect the signatures of selection in Sahiwal genome. The estimated p values were adjusted for multiple testing (FDR<5%). Gene annotations, QTL enrichment and functional analyses were carried out for identification of significant genomic regions. A total of 117 genes were annotated which affects a number of important economic traits. The QTL enrichment analysis highlighted 17 significant (FDR-corrected p value ≤ 0.05) regions on chromosomes BTA 1, 3, 6, 11, 20 and 21.The top three enriched QTLs were found on BTA 6, 20 and 23which are associated with exterior, health, milk, production and reproduction traits. Present study on selection signatures revealed a number of key genes related with coat color(PDGFRA, KIT, KDR), facial pigmentation (LEF), milk fat percent (MAP3K1, HADH, CYP2U1, SGMS2), sperm membrane integrity (OSTC), lactation persistency (MRPS30, NNT, CCL28, HMGCS1, NIM1K, ZNF131, CCDC152),milk yield (GHR, ZNF469), reproduction (NKX2-1, DENND1A) and Bovine Tuberculosis susceptibility (RNF144B, PAPSS1). Further analysis of candidate gene prioritization identified four hub genes, viz., KIT, KDR, MAP3K1 and LEF having role in coat color, facial pigmentation and milk fat percentage in cattle. Gene enrichment analysis revealed significant GO terms related to breed specific coat color and milk fat percent. The key genes and putative genomic regions associated with milk composition and coat color were identified in Sahiwal. It revealed selection for milk production, coat color and adaptability to tropical climate. The information on candidate genes can be utilized for further genetic improvement.